Impacts of GIC on the New Zealand Gas Pipeline Network. Issue 12 (15th December 2022) - Ingham, M.; Divett, T.; Rodger, C. J.; Sigley, M.
Abstract: Geomagnetically induced currents produced during geomagnetic storms present a potential risk to gas pipeline systems by disturbing the cathodic protection (CP) systems used to protect the pipeline from corrosion. In this study we look at CP monitoring data from a number of sites on the gas pipeline network in the North Island of New Zealand. We focus on variations during geomagnetic storms in three aspects of the CP system: (a) the output voltage of the constant current rectifiers, (b) the potential between the pipe and a Cu/CuSO4 reference cell, and (c) the potential between an installed metal coupon and the reference cell. The industry standard for suitable CP is that the latter potential should lie between −0.85 and −1.2 V when the rectifier is momentarily turned off. Three monitoring sites in particular are identified as showing very large variations in rectifier output voltage during geomagnetic storms, suggesting a possible risk to the system at these sites. Additionally, one of the three sites has coupon potentials which appear to rise above the −0.85 V level. Magnetotelluric impedance data are used to assess how effects at the monitoring sites relate to the magnitude and direction of induced electric fields. It clear that the response at any monitoring site is related to effects on the pipeline network as a whole. We also note the risks of disbonding and hydrogen induced cracking, issues we do not believe have been widely recognized in the research community. Plain Language Summary: Variations in Earth's magnetic field during geomagnetic storms induce electric currents (geomagnetically induced currents—GIC) in the ground which, in certain circumstances, may disrupt the cathodic protection (CP) systems used to protect buried gas pipelines from corrosion. In this study we examine monitoring data from the CP system on the gas pipeline network in the North Island of New Zealand to assess where GIC may present a possible threat to the integrity of the network. We identify four locations where significant variations in monitoring data occur in response to geomagnetic field variations and where additional monitoring is desirable. There appears to be a potential risk to the pipeline system at these sites. It is apparent that the complex geology and tectonics of New Zealand has a major influence on how GIC affect the pipeline network. Key Points: Variations in cathodic protection (CP) monitoring data on the New Zealand gas pipeline network during geomagnetic storms are reported Three locations are identified as having variations which suggest that during large storms the level of CP may be compromised At any location the CP system responds to electric fields across the whole pipeline network and not to local electric field orientation